International Council of Nurses: putting nurses at the centre of the world's policymaking has benefits for us all. (20th August 2019) - Catton, Howard
Abstract: This year's International Council of Nurses Congress in Singapore was an opportunity for nurses from around the world to discuss and shape policy and practice around the world. The World Health Organization recognises ICN's unique ability to influence its policies, represent nursing and help with the challenges that lie ahead, including a potential shortfall of nine million nurses by 2030. All nurses can get involved in efforts to raise the profile of the profession and attract a new generation who will continue to maintain the high standards expected of registered nurses for decades to come.